The politics of Andalusia, the days of the prince Muhammad bin Abdul Rahman (middle) 238-273 AH 886 852 / AD (Journal of the College of Basic Education, 2023)
Prayers and peace be upon our master Muhammad, the most honorable of the prophets and messengers, and upon his family and companions, and after: This research deals with an important period in the history of the Arab Islamic state in Andalusia, when Emirate Muhammad bin Abd al-Rahman “the second”, after the death of his father, who left the country calm and the pillars consolidated. Prince Muhammad bin Abd al-Rahman bin al-Hakam strengthened the pillars of the state, with all the work that he carried out, whether in the administrative, architectural or military aspect, foremost among which is the development of the naval fleet in